Swelling Pressure of Double-Expansive Material and Its Active Support Effect for Coal Seam Gas Drainage Borehole - Zhiming Wang; Yuning Sun (Advances in Materials Science and Engineering)
To improve coal seam gas drainage performance, we developed a double-expansive (DE) material to seal the borehole. The swelling process of this material includes an initial swelling stage and a secondary swelling stage. We studied the swelling pressure properties of the DE material under four constraint conditions using a self-made swelling test device. Further, the active support effect of the DE material on the borehole was analyzed by simulating borehole stability with COMSOL Multiphysics software. The results exhibit the following: (1) The swelling pressure of the DE material exhibits time-dependent behavior, and the mathematical relationship between the swelling pressure and time can be obtained by nonlinear fitting. (2) The radial swelling potential is principally formed during the secondary swelling stage, providing the main active support on the radial constraint. (3) The active support imposed on the hole wall can prevent the extension of plastic and damage regions around the borehole, for improved stability of the gas drainage borehole. Finally, field tests demonstrate improved gas drainage performance of the borehole sealed by the DE material compared to a conventional sealing material.